Duration of effect of interferon aerosol prophylaxis of vesicular stomatitis virus infection in mice. - Wyde, P R (1985)
Mice were exposed for 8 h to continuous small-particle aerosols containing natural mouse alpha interferon (estimated dosage 100 U per mouse) or one of two concentrations of hybrid recombinant alpha interferon A/D bgl (estimated dosages of 100 and 10,000 U per mouse, respectively). On days 1, 3, 5, 7, and 9 after exposure to these interferons, three mice from each group were inoculated intranasally with 100 PFU of vesicular stomatitis virus. Control mice were exposed to aerosols of saline or inoculated intraperitoneally with either natural mouse alpha interferon (350 U) or one of two doses of hybrid recombinant alpha interferon A/D bgl (350 or 35,000 U) and challenged similarly. Of mice injected intraperitoneally, only those given 35,000 U of hybrid recombinant alpha interferon A/D bgl 24 h before virus challenge were protected from pulmonary infection, compared with the saline-treated control mice. Of mice given 100 U of either interferon by small-particle aerosol, only those exposed 24 h before inoculation of vesicular stomatitis virus had reduced pulmonary titers of the virus. However, of mice given ca. 10,000 U of hybrid recombinant alpha interferon A/D bgl by small-particle aerosol, all groups except those exposed 9 days before virus inoculation had significantly reduced lung virus titers.